Population Dynamics and Regional Social Security Sustainability in Italy. Issue 1 (2nd January 2016) - Bonasia, Mariangela; De Siano, Rita
Abstract : Bonasia M. and De Siano R. Population dynamics and regional social security sustainability in Italy, Regional Studies . Making due allowances for differences in demographics, the labour market and internal migration dynamics, this study analyses the sustainability of the Italian pension balance at a regional level. A worsening of the elderly dependency ratio and a decline in birth and employment rates have generated a negative trend, particularly for regions in southern Italy, characterized by early retirement and an increase in migration outflows. The suggestion is that a decentralized pension policy is not a Pareto-efficient solution because it would favour the sustainability of the pension balance in northern regions over those in the South.